The role of internal control in preventing and combating workplace bullying in the brazilian public service - Oliveira, Elen Kelem da Silva Pereira de; Pinho Filho, Lúcio Carlos de; Costa, Danilo da (Revista Coleta Científica, 2026)
This capstone project investigates the role of internal control in preventing and combating workplace bullying in the Brazilian public service, focusing on promoting ethical governance and protecting civil servants' dignity. The research, based on bibliographic and documentary analysis, covers the period from 2019 to 2025, with an empirical data cutoff in February 2025, considering the availability of public reports and information from the Controladoria-Geral do Estado de Goiás (CGE/GO) and other control bodies. It analyzes the conceptual evolution of workplace bullying, the legal and jurisprudential framework, prevention and combat strategies, and the role of internal control as an agent of change. Emphasis is placed on humanized mechanisms, such as the Termo de Ajustamento de Conduta (TAC) and administrative mediation, in contrast to the rigidity of traditional Disciplinary Administrative Proceedings (PAD), which often cause additional suffering to civil servants. Data from CGE/GO reveals an increase in adherence to these consensual instruments, with a 38.4% growth in TACs in 2024 and the signing of 11 Termos Circunstanciados Administrativos (TCAs), indicating a trend towards more efficient and less costly resolution. It is concluded that internal control, by integrating organizational climate audits, psychosocial risk management, and ethical governance indicators, plays a crucial role in building a healthy and ethical work environment, essential for the efficiency and legitimacy of Public Administration.